Implementation of Character Education to Improve the Students Discipline Through Habituation of Nadzam Asmaul Husna Recitation at Grade IV - Asih, Puji; Sunarso, Ali (Elementary School Teacher, 2019)
Character education should take place through habituation and all the time in everyday life. This study aims was to determine (1) Implementation of character education (2) Barriers to Reading Asmaul Husna's Habits (3) Supporting reading habits Asmaul Husna (4) Influence of Asmaul Husna on student character. The research was conducted in SDN Purwoyoso 01 Ngaliyan with research subject of fourth-grade students, religious teachers and class teachers on Implementation of Student Discipline Character Education through Reading Asmaul Husna Habituation. The approach used was a qualitative single-case study type. Data collection was done through semi-structured interviews, observation, and documentation. Data analysis was done by using content analysis technique. The result of this research shows that: (1) the discipline of students is good, (2) the implementation of character education through reading habits of Asmaul Husna is good (3) the influence of reading habits of Asmaul Husna has an effect on the character of the students of class IV.